2019
DOI: 10.7759/cureus.6288
|View full text |Cite
|
Sign up to set email alerts
|

Elective Neck Dissection, but Not Adjuvant Radiation Therapy, Improves Survival in Stage I and II Oral Tongue Cancer with Depth of Invasion >4 mm

Abstract: In early-stage, node negative oral tongue cancer, there is limited data supporting tumor depth of invasion (DOI) as an indication for post-operative radiotherapy (PORT) to the primary site. The primary aim of this study is to examine the effect of tumor DOI and PORT on overall survival (OS). Materials and methods The National Cancer Database (NCDB) was used to query patients with AJCC stage I and II oral tongue cancer (2006-2013). Patients were stratified by receipt of PORT, elective neck dissection (ND), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…After DOI was included in the AJCC pT staging, most recent studies for OSCC and OTSCC have incorporated clear definitions of DOI and TT using the criteria proposed by the AJCC 12,13,15,20–22,27,28 . However, studies which have confused these two measurements 11 or did not provide a definition 14,27,29–31 continued to be reported in the literature. Additionally, a recent survey of 159 surgeons has shown that 18% of survey participants confused the definition of DOI with TT 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After DOI was included in the AJCC pT staging, most recent studies for OSCC and OTSCC have incorporated clear definitions of DOI and TT using the criteria proposed by the AJCC 12,13,15,20–22,27,28 . However, studies which have confused these two measurements 11 or did not provide a definition 14,27,29–31 continued to be reported in the literature. Additionally, a recent survey of 159 surgeons has shown that 18% of survey participants confused the definition of DOI with TT 10 …”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of 159 surgeons has shown that 18% of the survey participants define DOI as the distance from the mucosal surface of the tumour to the deepest point of invasion, which is the exact definition of TT 10 . Additionally, a large retrospective study published in 2019 has defined DOI using the criterion of TT as length measured from the tumour surface to the deepest point of invasion 11 …”
Section: Introductionmentioning
confidence: 99%
“…Because of its relevance regarding outcome and the presence of LM, preoperative and adjuvant choice of therapeutic options, especially elective neck dissection, should take DOI into consideration. Though, due to contradicting reports [56,57], it remains unclear, how to identify patients, especially with early-stage cancer, that would benefit from elective neck dissection. Several methods of evaluating DOI during the pretherapeutic staging process have been evaluated.…”
Section: Depth Of Invasionmentioning
confidence: 99%
“…The gold standard for stages I‐II OTSCC is transoral surgical excision with elective neck dissection if the pathological depth of invasion (DOI) is more than 4 and up to 9 mm 9,10 . Stages III‐IV OTSCC, with a DOI ≥10 mm, should be managed by “en‐bloc” tumor removal and concomitant neck dissection carrying out a so called standard wide margins surgery (SWMS) or, alternatively, a compartmental surgery (CTS) approach 11 .…”
Section: Introductionmentioning
confidence: 99%